Limbal stem cells: The search for a marker - Chee, K.Y.H.; Kicic, Anthony; Wiffen, S.J. (2006)
The corneal epithelium is a self-renewing tissue and must, by definition, have a resident basal cell population necessary for homeostasis and wound healing. There is a substantial body of evidence, both experimental and clinical, pointing to the basal cells of the limbus as the location of corneal epithelial stem cells. However, in the absence of a definitive marker of limbal stem cells, the evidence remains largely circumstantial. Many markers such as p63 and integrin α9 are preferentially localized to the limbus but cannot be regarded as stem cell-specific. Other markers such as K3 and connexin 43 can be regarded as markers of corneal differentiation. The discovery of stem cell markers in other organ systems, such as the haematopoietic system, offers optimism that a marker of limbal stem cells will one day be found. Such a discovery will have far-reaching implications for the study of ocular surface biology and stratified squamous epithelia in general. © 2006 Royal Australian and New Zealand College of Ophthalmologists.